Madani concept and its sustainability initiatives for MSMEs / Akma Hidayu Dol @ Abdul Wahid and Rafizan Abdul Razak - Dol@Abdul Wahid, Akma Hidayu; Abdul Razak, Rafizan (Universiti Teknologi MARA, Negeri Sembilan, 2023)
MADANI concept was officially introduced by Anwar on 19 January 2023. MADANI is not an everyday word used by Malaysians and the word itself is Arabic. What is the new slogan “Malaysia Madani” introduced by our Prime Minister Datuk Seri Anwar Ibrahim? Is this concept relevant to Micro, Small-Medium Enterprises (MSMEs)? The MADANI framework includes six core values namely sustainability, prosperity, innovation, respect, trust, and compassion.